1987
DOI: 10.1007/bf00177905
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and smoking: a perspective from animal studies

Abstract: Nicotine plays a key role in reinforcing tobacco smoking, and exerts several psychoneuropharmacological actions which may contribute to its reinforcing effects. Thus, nicotine can improve mood and alleviate withdrawal symptoms; it can also alter CNS arousal, reduce stress, suppress appetite, and improve performance on certain tasks. Behavioural studies in animals have tended to corroborate existing theories of smoking behaviour, and have started to suggest how and where nicotine may exert its central actions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 72 publications
2
58
0
2
Order By: Relevance
“…One study reported performance to be similar between deprived smokers and nonsmokers (Warburton 1990). Finally, nicotine appears to improve the performance of animals not previously exposed to nicotine (Clarke 1987;Emley and Hutchinson 1984).…”
Section: Physical Activitymentioning
confidence: 99%
“…One study reported performance to be similar between deprived smokers and nonsmokers (Warburton 1990). Finally, nicotine appears to improve the performance of animals not previously exposed to nicotine (Clarke 1987;Emley and Hutchinson 1984).…”
Section: Physical Activitymentioning
confidence: 99%
“…The interaction of nicotinic receptors with central muscarinic cholinergic receptors may be substantial, as nicotine has been shown to release ACh, probably onto postsynaptic muscarinic receptors (Rowell and Winkler 1984;Clarke et al 1987). Amnesia after mecamylamine administration has been correlated with decreases in regional brain ACh synthesis (Elrod and Buccafusco 1991).…”
Section: Effects Of Mecamylamine On Cognition 103mentioning
confidence: 99%
“…Previous studies have shown that the locomotor activating effect of nicotine becomes more marked upon repeated administration of the drug (Clarke & Kumar, 1983;Ksir et al, 1985;1987). Similarly, the locomotor stimulant effect of amphetamine, which is also mediated through increases in extracellular dopamine in the accumbens, can show sensitization after amphetamine is administered repeatedly (Robinson & Becker, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine has a broad spectrum of behavioural effects, including the ability to serve as a positive reinforcer and as a discriminative stimulus, and to promote changes in rates of both conditioned and unconditioned behaviour (Clarke, 1987;Stolerman, 1990). Recent investigations have compared the behavioural effects of (-)-nicotine with those of other nicotinic agonists to determine whether each agonist exhibits the whole spectrum of effects shown by nicotine.…”
Section: Introductionmentioning
confidence: 99%